Managing agricultural enterprises and developing agricultural value chains: Cases on agribusinesses - Kolavalli, Shashidhara; Naik, Gopal; Tsamenyi, Mathew; Babu, Suresh Chandra (Springer, 2024)
This book of cases, mostly of small to medium organizations, from west Africa, Thailand and India offers cases suitable for training of practicing managers of small and medium agricultural enterprises and public sector professionals engaged in agricultural development. The book comprises an introductory essay, 22 cases, two industry notes, and a chapter guiding how the cases may be used to develop a one- or two-week training program. The cases are situations in enterprises or sectors that require a decision to be made, written from the perspective of a protagonist, usually a high-level decision maker. The cases included in the book are predominantly from West Africa—Ghana, Cote d’Ivoire, and Nigeria—and the rest are from India. In addition, two industry notes, one on tomato processing in Turkey and the other on the maize seed industry in Thailand are included. They offer contrasting situations to those addressed in some of the west African cases. Case-based teaching is particularly suitable for training of practicing managers with limited formal training. The cases in the book are adequate to comprehensively address key issues in agricultural enterprise management and value chain development.